Memorandum di Masa Pemerintahan Abdurrahman Wahid dalam Perspektif Hukum Tata Negara Islam - Misbahuddin Misbahuddin (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2019)
The tide of democratization in Indonesia has radically changed the structure of Indonesian politics since the overthrown of New Order government by the reform movement in 1998. One important change is the essential vitality of parliamentary politics in Indonesia. In the era of Abdurrahman Wahid's government, the DPR's role was more independent and had a loud voice constraining the executive's running. As a result, the Indonesian constitution which is based on the Presidential system seems to have deviated to being a Parliamentary System. An example of tension is the birth of a memorandum. This paper seeks to examine the "Memorandum during the Government of Abdurrahman Wahid" from the perspective of Islamic State Administration Law. This paper concludes based on the Islamic State Administration Law that the Abdurrahman Wahid's Government Memorandum is invalid because the warning or redressal requirements for a president must be preceded by evidence of deviation from religion.